El cuento de hadas para la comprensión lectora de los niños y niñas de tercer año de educación básica, de la unidad educativa internacional liceo iberoamericano del cantón Riobamba, provincia de Chimborazo, periodo 2015-2016 - Cuadrado Moncayo, Fernanda Carolina (2016)
Research comes of the principle of all inquiry because it allows establishing the causes and effects of learning problems that have boys and girls of third year of Basic Education, of International Educational Unit "Liceo Iberoamericano". It is proposed the following general objective: to determine the influence of fairy tales for reading comprehension of boys and girls of third year of Basic Education, of International Educational Unit "Liceo Iberoamericano" in the period 2015-2016, through research and observation sheets in order to achieve significant learning in children. It is organized with the theoretical framework for investigating topics such as the fairy tale, also with reading comprehension to support this thesis. Inductive-deductive method was used, this method examines the particularities that have occurred in the reading comprehension process of boys and girls in third year of basic, and the observation technique was applied. It was used the group observation sheets to collect information about the variables, the fairy tale for reading comprehension, in which the relevant research study very clearly is determined. The study population was 20 boys and girls, the observation results were analyzed and interpreted. Then it was reached the conclusions and recommendations, which reflect the importance and impact of fairy tales for reading comprehension. It was also performed classroom activities, which allowed students are motivates by reading stories because they are playful activities which favors the development of imagination, creativity and language.